The lighthouse family. The turtle - Rylant, Cynthia (Rylant, Cynthia. Lighthouse family., 2006)
Pandora the cat, Seabold the dog, and their three adopted mouse children, call on the pelicans for help when Aurora the sea turtle becomes stranded in fog and cold water near the lighthouse.